CREATIVE PROCESS OF WRITING THE DRAMA SCRIPT KABAYAN NGALANGLANG JAMAN BY ROSYID E. ABBY - Trihandayani, Rista; Anoegrajekti, Novi; Yarmi, Gusti (Erudio Journal of Educational Innovation, 2023)
This research aims to gain a profound understanding of the creative process in writing the Kabayan Ngalanglang Jaman drama script by Rosyid E. Abby, using Rhodes' creativity theory, which consists of the 4P framework (person, press, process, and product). The study aims to explore the author's social background and ideology. This study is a qualitative research conducted through content analysis. The research instruments employed for this study were interviews and documentation, designed to collect research data. Data analysis techniques included data reduction, data presentation, and drawing conclusions. The findings of this research reveal that the author fulfills all 14 criteria for being a creative person. The author is motivated by both internal and external factors when writing the script. The creative process employed by the author can be divided into three stages: activities before writing, activities during writing, and activities after writing, resulting in the creative steps taken by the author in writing the drama script. The creative product generated by the author also meets three criteria for creative products. Through the creative process, social-cultural background and the author's ideology in writing the Kabayan Ngalanglang Jaman script are identified.